2015
DOI: 10.1371/journal.pone.0134897
|View full text |Cite
|
Sign up to set email alerts
|

A Genomic Approach to Unravel Host-Pathogen Interaction in Chelonians: The Example of Testudinid Herpesvirus 3

Abstract: We report the first de novo sequence assembly and analysis of the genome of Testudinid herpesvirus 3 (TeHV3), one of the most pathogenic chelonian herpesviruses. The genome of TeHV3 is at least 150,080 nucleotides long, is arranged in a type D configuration and comprises at least 102 open reading frames extensively co-linear with those of Human herpesvirus 1. Consistently, the phylogenetic analysis positions TeHV3 among the Alphaherpesvirinae, closely associated with Chelonid herpesvirus 5, a Scutavirus. To da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 52 publications
0
31
1
Order By: Relevance
“…Historically, viral causes of disease in reptiles were likely to be under-reported for many reasons including the cost and bioinformatics support required to investigate novel diseases using NGS technologies, as well as co-infections with microbial species, and poor sampling techniques that obscure the true aetiologic agent [6]. Pathogen discovery tools, which are not reliant on targeting a specific organism, are increasingly being used in wildlife disease investigations [10,17,53,54], although uptake is considered slow comparative to health research in humans and domestic animals [54]. Thus we anticipate an increase in the number of viruses detected in wildlife taxa that have had few viral disease investigations, such as lizards, compared to well-studied mammals such as bats, rodents and primates where their capacity to host zoonotic pathogens arguably provides public health drivers for research as well as funding incentives [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, viral causes of disease in reptiles were likely to be under-reported for many reasons including the cost and bioinformatics support required to investigate novel diseases using NGS technologies, as well as co-infections with microbial species, and poor sampling techniques that obscure the true aetiologic agent [6]. Pathogen discovery tools, which are not reliant on targeting a specific organism, are increasingly being used in wildlife disease investigations [10,17,53,54], although uptake is considered slow comparative to health research in humans and domestic animals [54]. Thus we anticipate an increase in the number of viruses detected in wildlife taxa that have had few viral disease investigations, such as lizards, compared to well-studied mammals such as bats, rodents and primates where their capacity to host zoonotic pathogens arguably provides public health drivers for research as well as funding incentives [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Viruses associated with respiratory disease in captive reptiles include the ferlaviruses [13], Ball python nidovirus [14] and an Indian python nidovirus [9], atadenoviruses and reoviruses [15], ranaviruses [16], and Sunshine virus [10]. Viruses causing respiratory pathology and reported in both captive and wild reptiles include herpesviruses in chelonians [17], and reoviruses in snakes and lizards [18,19]. Gram-negative bacterial respiratory infections are often described in captive reptiles, however are likely present as secondary or co-infections, and reflect the multi-factorial nature of disease in reptiles generally where environment, host and agent characteristics will result in a spectrum of clinical outcomes when individuals are exposed to aetiological agents [12].…”
Section: Introductionmentioning
confidence: 99%
“…Primers were designed to target the full-length sequence of three genes within the ChHV5 genome; 1) glycoprotein B (gB), 2) sialyltransferase (F-sial) and 3) DNA polymerase (DNApol). The DNApol gene has been used extensively to determine the presence or absence of ChHV5 [12,13,15,17,20,21,23,24,26,29,44] due to the highly conserved nature of the gene [45,46]. Conversely, the gB gene codes for glycoproteins which are located on the surface of the virion and therefore in contact with the host immune system, likely increasing selection pressure.…”
Section: Dna Extraction Primer Design and Polymerase Chain Reaction mentioning
confidence: 99%
“…Conversely, the gB gene codes for glycoproteins which are located on the surface of the virion and therefore in contact with the host immune system, likely increasing selection pressure. This antigenic nature of gB has led to sequence variability, making it an ideal candidate gene for phylogenetic studies [46][47][48]. Moreover, [28] demonstrated that this gene is effective in determining ChHV5 phylogeny in Australia.…”
Section: Dna Extraction Primer Design and Polymerase Chain Reaction mentioning
confidence: 99%
“…While this study was under review, a version of the strain 1976 genome sequence became available (59). In comparison with our sequence, this contains a 9,521-nt deletion (nt 5469 to 14989) starting in TE5 and ending near the left end of U L and thus lacks seven genes, including TE7 and TE8.…”
Section: Resultsmentioning
confidence: 99%